PENGARUH INOVASI TERHADAP KINERJA BISNIS PENJAHIT DI KECAMATAN TELUKDALAM KABUPATEN NIAS SELATAN - Kedepan Rohanus Sarumaha (Universitas Nias Raya, 2022)
A small sewing business is an economical “business” “that” “stands” “alone” and “is” run “by” “an” “individual” “or” “business” “entity” “that” “is” “not” a “subsidiary” “or” “branch” “of” a “company” “that” “is” “owned,” “controlled,” or “part” “of” a medium or large company, either directly or indirectly. “The” “purpose” “of” “this” research is to find out how innovation affects the performance of the tailor business in Telukdalam District, South Nias Regency. The research method used is causal quantitative research. The data source is tailors who have a population of 65 people, and the sample size in this study is 40 people. Data collection methods include research tools and surveys. “Data” “were” “analyzed” “using” “simple” “linear” “regression” “analysis.” From “the” research “results” it is known “that” “the” value “of” t count (4.990) > t table is (1.686). This study concludes “that” “there” “is” “an” “impact” “of” “innovation” “on” “the” performance “of” “the” tailor business in Telukdalam District, South Nias Regency. The suggestions for this research are (1) Entrepreneurs must obtain maximum ability in the sewing business so that business performance can increase. (2) Sewing pattern formation training is needed to improve sewing skills.